2019
DOI: 10.21106/ijma.326
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Gender and Maternal and Child Health Injustices through Faith Community-Led Initiatives

Abstract: Background and Objective: Congregational Health Empowerment and Social Safety Advocates (CHESSAdvocates) initiative, a project aimed at mitigating maternal and child health (MCH) and gender injustices in religiously pluralistic societies, was implemented in two Northern Nigerian states of Benue and Kaduna between September 2018 and July 2019. The objective of this study was to assess the effectiveness, sustainability and factors of success in the CHESS-Advocates model as a faith community approach to mitigatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…De Allegri et al [ 34 ], found a negative association between traditional African religions and ANC uptake. Conversely, a study by Nwakamma et al [ 37 ], found that introducing and connecting women to ANC services through faith-based communities and leaders was an important factor in promoting ANC.…”
Section: Resultsmentioning
confidence: 99%
“…De Allegri et al [ 34 ], found a negative association between traditional African religions and ANC uptake. Conversely, a study by Nwakamma et al [ 37 ], found that introducing and connecting women to ANC services through faith-based communities and leaders was an important factor in promoting ANC.…”
Section: Resultsmentioning
confidence: 99%